Assessment of water contamination caused by a mutagenic textile effluent/dyehouse effluent bearing disperse dyes - Carneiro, Patricia A. [UNESP]; Umbuzeiro, Gisela A.; Oliveira, Danielle P.; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2010)
High performance liquid chromatography coupled to a diode array detector method was developed to detect disperse dyes in water samples over the range 0.50-35 ng,with detection limits of 0.09 ng, 0.84 ng and 0.08 ng, respectively, with good repeatability and accuracy. This study identifies the disperse azo dyes C.I. Disperse Blue 373, C.I. Disperse Orange 37 and Disperse Violet 93 as components of a commercial dye formulation assigned as Dispersol Black Dye (CVS) used in the textile industry for dyeing synthetic fibers that are contributing to the mutagenicity found in the Cristais River, São Paulo, Brazil. High performance liquid chromatography coupled to a diode array detector was applied to monitor the occurrence of these dyes in: (1) the treated industrial effluent, (2) raw river water, (3) treated river water, and (4) the sludge produced by a Drinking Water Treatment Plant (DWTP) which is located 6 km downstream from the textile industrial discharge, where dyes' concentrations changed from 1.65 ng L(-1) to 316 mu L(-1). (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Disperse dyes; HPLC-DAD; Aquatic pollution; Monitoring of textile dye; Mutagenic compounds